2018
DOI: 10.1109/tit.2017.2786551
|View full text |Cite
|
Sign up to set email alerts
|

Information Structures for Feedback Capacity of Channels With Memory and Transmission Cost: Stochastic Optimal Control and Variational Equalities

Abstract: The Finite Transmission Feedback Information (FTFI) capacity is characterized for any class of channel conditional distributions P B i |B i−1 ,A i : i = 0, 1, . . . , n and P B i |B i−1 i−M ,A i : i = 0, 1, . . . , n , where M is the memory of the channel, B n = {B j : j = . . . , 0, 1, . . . , n} are the channel outputs and A n = {A j : j = . . . , 0, 1, . . . , n} are the channel inputs. The characterizations of FTFI capacity, are obtained by first identifying the information structures of the optimal channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…The starting point of our analysis is based on the information structures of the channel input conditional distribution developed in [11], and the convexity property of the extremum problem of feedback capacity derived in [10], [28] for abstract alphabet spaces and in [8] for finite alphabet spaces.…”
Section: ) Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The starting point of our analysis is based on the information structures of the channel input conditional distribution developed in [11], and the convexity property of the extremum problem of feedback capacity derived in [10], [28] for abstract alphabet spaces and in [8] for finite alphabet spaces.…”
Section: ) Methodologymentioning
confidence: 99%
“…In this paper, we utilize recent work found in [10], [11], to develop such a methodology. Specifically, we derive sequential necessary and sufficient conditions for channel input distributions to maximize the finite horizon directed information.…”
Section: Index Termsmentioning
confidence: 99%
“…where the transmission cost functions are either one of the following two classes 1 Transmission Cost Functions Class A. γ i (T i a n , T i b n ) = γ A i (a i , b i ), (I.7)…”
Section: A Contributionsmentioning
confidence: 99%
“…In [1], it is shown that the maximization of I(A n → B n ) over all distributions P A i |A i−1 ,B i−1 : i = 0, . .…”
Section: Equivalent Characterizations Of Ftfi Capacity For Class B Chmentioning
confidence: 99%
See 1 more Smart Citation